B-Cell Epitope Mapping of the Treponema pallidum Tp0435 Immunodominant Lipoprotein for Peptide-Based Syphilis Diagnostics - Jessica L. Keane; Mahashweta Bose; Barbara J. Molini; Kelika A. Konda; Silver K. Vargas; Michael Reyes Diaz; Carlos F. Caceres; Jeffrey D. Klausner; Rebecca S. Treger; Lorenzo Giacani (Diagnostics)
Background/Objectives: Syphilis, a chronic sexually transmitted disease caused by the spirochete Treponema pallidum subspecies pallidum (T. pallidum), is still endemic in low- and middle-income countries and has been resurgent for decades in many high-income nations despite being treatable. Improving our understanding of syphilis pathogenesis, immunology, and T. pallidum biology could result in novel measures to curtail syphilis spread, including new therapeutics, a preventive vaccine, and, most importantly, improved diagnostics. Methods: Using overlapping synthetic peptides spanning the length of the T. pallidum Tp0435 mature lipoprotein, an abundant antigen known to induce an immunodominant humoral response during both natural and experimental infection, we evaluated which Tp0435 linear epitopes are most significantly recognized by antibodies from an infected host. Specifically, we used sera from 63 patients with syphilis at different stages, sera from non-syphilis patients (n = 40), and sera longitudinally collected from 10 rabbits infected with either the Nichols or SS14 isolates of T. pallidum, which represent the model strains for the two known circulating clades of this pathogen, to further evaluate the use of this animal model for syphilis studies. Recognized amino acid sequences were then mapped to the experimentally determined Tp0435 structure. Results: Reactive epitopes in both serum groups mapped predominantly to the α-helix preceding Tp0435 soluble β-barrel and the loops of the barrel. Conclusions: In the current effort to improve current syphilis diagnostics, the peptides corresponding to these immunodominant epitopes could help develop epitope-based assays such as peptide-based ELISAs and lateral flow point-of-care tests to improve the performance of treponemal tests and expedite diagnosis in low-income settings, where the infection is still a significant concern for public health and access to facilities with laboratories equipped to perform complex procedures might be challenging.